An encyclopaedia of civil engineering historical, theoretical, and practical. Volume 1 - Cresy, Edward, 1792-1858 (Thomas Telford, 2010)
Edward Cresy, the renowned architectural historian and civil engineer, has drawn on his incredible vision and breadth of knowledge to bring together a remarkable history of civil engineering. First published in 1847 this facsimile edition of the first part of his encyclopaedia includes a vast number of illustrations, a history of civil engineering by period and a glimpse into the theory and practices of the day.